2011
DOI: 10.1248/yakushi.131.901
|View full text |Cite
|
Sign up to set email alerts
|

The Present Condition of Diabetes and Its Treatment-From the Perspective of a Hospital Pharmacist-

Abstract: In Japan, the number of diabetic patients has increased steadily. According to a 2007 report by the Ministry of Health, Labour and Welfare, the number of diabetic patients and its reserves is estimated to be 22 million, or aˆfth of adults. On a global scale, the number of deaths due to diabetes is almost equivalent to that due to AIDS. Therefore, in 2006, WHO designated November 14 as World Diabetes Day and began a worldwide campaign to increase people's awareness of diabetes. Diabetic patients usually ‰uctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…= 5.1%, n = 5). The concentration of GA in the diluted sample was 1.0 × 10 −12 M. Although this concentration was lower than those commonly reported, 30,31) the value was in agreement with the value of 0.6-3% for GA. 32) As a result, this procedure could be a form of sensing for GA in serum samples.…”
Section: Resultssupporting
confidence: 87%
“…= 5.1%, n = 5). The concentration of GA in the diluted sample was 1.0 × 10 −12 M. Although this concentration was lower than those commonly reported, 30,31) the value was in agreement with the value of 0.6-3% for GA. 32) As a result, this procedure could be a form of sensing for GA in serum samples.…”
Section: Resultssupporting
confidence: 87%
“…If the exponential curve for the percentage of donors with GA ≥16.5 (Figure 2) is extrapolated to people aged ≥70 years, the number of people with prediabetes/diabetes would be 6.5 million in total. There are two possible reasons for the considerable difference in the projected number of people with prediabetes/diabetes between the current study and the governmental research report 2 based on HbA 1c levels (22.1 million). First, the reference range for GA was determined as three times the reference range for HbA 1c in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…In Japan, a nationwide study on the prevalence of diabetes mellitus was carried out by the Ministry of Health, Labour and Welfare in 2007, and it was estimated that there were as many as 22.1 million people with diabetes or suspected diabetes 2 . Type 2 diabetes mellitus is thought to develop as a result of compound effects of hereditary factors, such as impaired insulin secretion or insulin resistance, and various lifestyle factors, such as overeating, lack of physical activity and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…After 6 months of DTES by pharmacists, the post-test data showed that there was signi cant difference between patients in the intervention group and the control group in the score distribution: the score distribution of the intervention group was in the range of 80-99 and the number of patients with low score was reduced remarkably, while the score distribution of the control group was in the range of 60-79. This indicated that under the pharmacists' work, the diabetes knowledge of patients in the intervention group was signi cantly improved 32,35,36 .…”
Section: Discussionmentioning
confidence: 96%